Fraud Hexagon Sebagai Model Deteksi Dini Kecurangan Pelaporan Keuangan - Ervin Arif Setiawan; Melati Oktafiyani; Agung Prajanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
One of the important components of an accounting information system is the annual financial report, which is used to present data on the financial condition, operational results, and cash flows of a company over a specific period of time. This study aims to understand the impact of the fraud hexagon, comprising pressure, opportunity, rationalization, capability, arrogance, and collusion on financial statement fraud. The method used in this study is purposive sampling, with subjects drawn from companies in the banking sector that prepared annual reports within the period of 2022–2024. The data analyzed were obtained from secondary sources retrieved from the Indonesia Stock Exchange and the official websites of each company, with a total sample of 96. To analyze the data, WarpPLS 7.0 was used to test the influence of the fraud hexagon on financial statement fraud. The findings of this study reveal that the factors influencing financial statement fraud are Weak Oversight Mechanisms (X3) and Collusion (X7) measured by the presence of commissioners holding concurrent positions. Meanwhile, factors such as Financial Stability (X1), measured by the Loan to Deposit Ratio (LDR), External Pressure (X2), measured by Non-Performing Loans (NPL), Auditor Turnover (X4), Board of Directors Turnover (X5), and Arrogance (X6), measured by the number of CEO photos included in the annual report, were found to have no effect on financial statement fraud.